2007
DOI: 10.1016/j.pain.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Studying sex and gender differences in pain and analgesia: A consensus report

Abstract: In September 2006, members of the Sex, Gender and Pain Special Interest Group of the International Association for the Study of Pain met to discuss the following: (1) what is known about sex and gender differences in pain and analgesia; (2) what are the "best practice" guidelines for pain research with respect to sex and gender; and (3) what are the crucial questions to address in the near future? The resulting consensus presented herein includes input from basic science, clinical and psychosocial pain resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
645
9
39

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 871 publications
(718 citation statements)
references
References 206 publications
(274 reference statements)
25
645
9
39
Order By: Relevance
“…Previous research has indicated a sex difference in pain perception for some species and gonadal hormones are known to have an effect on pain responses (Greenspan et al, 2007). No such effect of sex per se (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research has indicated a sex difference in pain perception for some species and gonadal hormones are known to have an effect on pain responses (Greenspan et al, 2007). No such effect of sex per se (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…It has been found to differ based upon general characteristics such as age (rats: Gagliese and Melzack, 2000) and sex (Greenspan et al, 2007). Complex interactions between two or more factors are also evident such as sex and age (sheep: Guesgen et al, 2011) or age and body weight (piglets: Janczak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of gender on the reporting and experience of pain has been well documented 19 . Studies have shown quite consistently that the population prevalence of pain is higher in females.…”
Section: Correlates Of Painmentioning
confidence: 99%
“…However, despite the generally accepted view that females are more sensitive than males (Greenspan et al, 2007), the underlying cause is not clear and indeed, may be multifactorial. In women, one factor that appears to affect the pain experience is the cyclical variations in sex hormones that occur during the menstrual cycle.…”
Section: Introductionmentioning
confidence: 97%